Pengaruh Hybrid Learning pada Mata Kuliah Telaah Drama: Studi Kasus KS Ku-Liek - Kartika, Gisti (Universitas Negeri Padang, 2023)
This research refers to the hybrid learning method applied to the Indonesian Drama Review course taken by students of the Indonesian Literature study program, Faculty of Language and Arts, Universitas Negeri Padang class of 2020 in the fourth semester of lectures. In practice, students experience many obstacles so they have to ask for help from an art community called Ku-Liek Art Community (KS Ku-Liek). This research method is a qualitative method with a case study approach model. Research participants were selected using purposive techniques with the help of key persons consisting of Indonesian Literature students and the Ku-Liek Art Community management board. The data collection method used interviews and observations. The results obtained were (1) the influence of hybrid learning in encouraging the independence of Indonesian literature students for the development of the Drama Studies course, (2) the role and quality of KS Ku-Liek in helping students to succeed in the Drama Studies course, and (3) the influence of hybrid learning in providing opportunities for the development and promotion of KS Ku-Liek. The hybrid method is considered effective in encouraging students to be more independent, and creating opportunities for art communities that are oriented towards improving the quality of education.